Effect of interventional edge-to-edge repair in tricuspid regurgitation on dimensions of the annulus. (4th February 2022) - Goebel, B; Salomon, C; Abdulrahman, M; Richter, S; El Garhy, M; Costello-Boerrigter, L; Lapp, H; Lauten, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The technique of percutaneous tricuspid valve edge-to-edge repair (pTVR) depends upon the connection of leaflets in the area of regurgitation using a coaptation device. By closing the coaptation device a considerable tractive force is applied on the leaflets, which might have an effect on the valve annulus. The aim of this study was to examine the impact of device implantation on tricuspid annular dimensions. Methods: During pTVR, 3D zoom loops of the tricuspid valve (TV) were acquired before and after clip placement using transesophageal echocardiography. Measurements of TV annular dimensions included the following parameters: annulus area (TV area), maximal diameter, minimal diameter, and eccentricity index (Figure 1). Tenting area was derived from a four-chamber view of the valve. Tricuspid regurgitation (TR) severity was graded from 1+ to 5+ by measuring vena contracta area (VCA3D) in 3D full volume color Doppler loop using multiplanar reconstruction.  Right atrial (RA) and ventricular volumes (RVVd3D, RVVs3D) and function (RVEF3D) were assessed in a 3D full volume loop. Results: The study population consisted of 97 patients (age 78 ± 6 years, 47 male), undergoing pTVR at our hospital. As expected, cavity dimension correlated with TV area size (for RVVd3D r = 0.51, p < 0.001 and for RA volume r = 0.71, p < 0.001). The mean TV annular area was significantly reduced (Annular area 8.53 ± 2.23 cm²/m²BSA vs. 7.55 ± 2.18 cm²/m²BSA, p < 0.001) and the shape of the annulus became more oval (Eccentricity index 1.2 ± 0.15 vs. 1.29 ± 0.17, p < 0.001) after pTVR. The reduction in annular area (12 ± 7%, range 0.7-28%) was only modestly correlated with the number of implanted coaptation devices (r = 0.30, p < 0.001) and the percentage reduction of VCA3D (r =0.36, p < 0.001). In the patient group with an annular area change ≥12%, a decrease in TR grade to ≤2+ by pTVR was achieved in 83% of cases, whereas only 62% of patients achieved moderate TR when the change in area was below 12%. Conclusion:   pTVR using coaptation devices reduces the area of the TV annulus. This effect may be modestly correlated to the number of devices implanted.